ANALISIS VEGETASI MANGROVE DI EKOSISTEM MANGROVE DESA TAPIAN NAULI I KECAMATAN TAPIAN NAULI KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA - Hotden P. Simamora; Khairijon '; Mayta Novaliza Isda (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Mangrove is vegetation that grows at the low tide area and the coastal region. A vegetation research analysis of mangrove had been done in Tapian Nauli I Village, Tapanuli, North Sumatra Province from April to May 2013. The aim of this study was to analyze the vegetation of mangrove forest. The method used in this study was a survey method, using a nested sampling. The parameters observed in this research were species compositions and important value index. The result showed that six mangrove species were identified. The highest density for seedling (26%) and for sapling stage (23%) were found at Avicennia marina, while for tree stage (30%)was found at Rhizophora apiculata. The highest dominance for seedling and sapling stage were found at Aveicennia marina and Rhizophora apiculata(24%), while for tree was found at Rhizophora apiculata (28%). The highest frequency for seedling (28,47% ) and sapling (27,47%) were found at R. marina while for tree stage was found at Rhizophora apiculata (28.46%). The highest importance value index at seedling (78,47%) and sapling stage (74,27%) were found at Aveicennia marina while for the tree stage was found at Rhizophora apiculata (86.46%).